Down‐slope facies variability within deep‐water channel systems: Insights from the Upper Cretaceous Cerro Toro Formation, southern Patagonia. Issue 6 (30th March 2018) - Malkowski, Matthew A.; Jobe, Zane R.; Sharman, Glenn R.; Graham, Stephan A.
Abstract: In southern Patagonia, outcrops of the Upper Cretaceous Cerro Toro Formation preserve a >150 km long deep‐water axial channel belt in the Magallanes–Austral Basin, providing a unique opportunity to investigate longitudinal variations in the depositional characteristics of a deep‐water channel system. This study documents sedimentological, stratigraphical and geochronological data from the Cerro Toro Formation in the Argentine sector of the basin. New results are integrated with previous work from the Chilean basin sector to conduct a basin‐scale comparison of the timing of deposition, provenance and lithofacies proportions. The Cerro Toro channel belt includes a nearly 1000 m thick section characterized by high‐density turbidites and mass‐wasting deposits. Two ash beds from the base of the section yield U–Pb zircon ages of 90·4 ± 2 Ma and 88·0 ± 3 Ma, indicating similar initiation ages as documented in the Chilean sector. The U–Pb detrital zircon age spectra from samples in the study area reveal similar provenance trends to samples from the Chilean basin sector, with peak age populations at 310 to 260 Ma, 160 to 135 Ma and 110 to 82 Ma. The maximum depositional age of the channel belt in the Argentine sector is 87·8 ± 1·5 Ma and all new geochronology data corroborate an 86 to 80 Ma depositional age for the main Cerro Toro channel belt. Statistical analyses of 7370 beds from nearly 8000 m of new and previously published stratigraphic sections along the entire outcrop belt suggest progressive variations in the down‐system proportion of lithofacies. In the up‐slope region, lithofacies representing mass wasting processes (for example, debris‐flow and mass‐transport deposits) account for ca 29% of the stratigraphic thickness, as opposed to 5% in the down‐slope region of the channel belt, where turbidity current deposits are more prevalent. The proportion of beds >1 m thick also decreases systematically down slope, particularly for conglomeratic turbidite deposits. This work highlights that: (i) the proportion of thick beds and distribution of lithofacies are key down‐system changes in the stratigraphic fill of this deep‐water channel belt; (ii) detrital zircon trends suggest a relatively well‐mixed longitudinal depositional system; and (iii) geochronology of the main Cerro Toro outcrop belt supports but does not necessitate the model of a single, roughly age‐equivalent, channel system. This study has implications for understanding the downslope variability in depositional processes, stratigraphic architecture and reservoir quality of submarine channel systems.